Mfumo Dume - Chanzo cha Ufungwa wa Mwanamume: Uhakiki wa Semi Kutoka Jamii za Kiafrika (JULACE: Journal of the University of Namibia Language Centre, 2020)
Numerous studies have been done on the patriarchy system, especially on how it affects women. However, there is a void when it comes to how the system affects men who are part of the society within which it has taken root. This paper, through various African sayings, carries a discussion on how patriarchy system has affected men and as a result they have found themselves in various types of confinements such as mental, emotional, cultural and financial. This study, through the data provided reveals how this system has not only affected women but men as well, the later being its primary victims. Furthermore, it is revealed that in order for the women liberation movement to be a true success, men liberation from this system should not only be considered but it is a requirement of great importance. In conclusion, the study gives various suggestions such as developing oral literature programs with themes that can change young boy’s minds on how they perceive themselves, girls and their roles in a society. Findings suggest that the fight against this system should not be a fight of women against men (and/or vice versa) or women and some men fighting the system, rather it must be men and women fighting against the system that has ensalaved both of them for so long.
Keywords: patriarchy system; incarceration; African sayings; African societies